The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/plants10020309
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Adaptation to Water Salinity in Six Wild Halophytes Suitable for Mediterranean Agriculture

Abstract: Owing to the high interspecific biodiversity, halophytes have been regarded as a tool for understanding salt tolerance mechanisms in plants in view of their adaptation to climate change. The present study addressed the physiological response to salinity of six halophyte species common in the Mediterranean area: Artemisia absinthium, Artemisia vulgaris, Atriplex halimus, Chenopodium album, Salsola komarovii, and Sanguisorba minor. A 161-day pot experiment was conducted, watering the plants with solutions at inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…In a previous study [25], the perennial C4 shrub Atriplex halimus resulted as the most salt tolerant species among six wild halophytes common in the Mediterranean area.…”
Section: Introductionmentioning
confidence: 84%
“…In a previous study [25], the perennial C4 shrub Atriplex halimus resulted as the most salt tolerant species among six wild halophytes common in the Mediterranean area.…”
Section: Introductionmentioning
confidence: 84%
“…Land degradation resulting from salinity puts global agriculture in jeopardy, as it engulfs 3600 million hectares (Mha) out of 5200 Mha of world agricultural land, leading to the loss of USD 27.5 billion every year [ 1 , 2 ]. Furthermore, reports anticipate that the world population will increase to 9.7 billion by 2050, which would require 70% greater food production by that time, exerting additional pressure on the shrinking areas of agricultural land [ 3 ]. To feed the growing human population, many parts of the world in peril of drought are still using salt-contaminated ground water for irrigation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study is a first field investigation on the feasibility of growing agretti under organic- like growing conditions as a Se-biofortified crop under saline and B-irrigated field conditions in the westside of Central California. Previous studies have identified agretti as a potential halophyte crop for growing in saline conditions ( Colla et al, 2006 ; Calone et al, 2021 ), as well as in in saline/Se-rich soils and irrigating with Se-enriched water under greenhouse conditions ( Centofanti and Bañuelos, 2015 ; Zhu et al, 2019 ). In this field study, agretti was grown on Se-rich soil and irrigated with either low -saline water or with saline water naturally enriched with Se and B at different irrigation rates (% of ET o ).…”
Section: Discussionmentioning
confidence: 99%